Design Engineering, Parts a and B 2005
DOI: 10.1115/imece2005-80965
|View full text |Cite
|
Sign up to set email alerts
|

Monotonicity and Active Set Strategies in Probabilistic Design Optimization

Abstract: Probabilistic design optimization addresses the presence of uncertainty in design problems. Extensive studies on ReliabilityBased Design Optimization (RBDO), i.e., problems with random variables and probabilistic constraints, have focused on improving computational efficiency of estimating values for the probabilistic functions. In the presence of many probabilistic inequality constraints, computational costs can be reduced if probabilistic values are computed only for constraints that are known to be active o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…2, we begin with the sequential linear programming (SLP) algorithm for RBDO developed in Chan et al (2006Chan et al ( , 2007. Since the objective function is deterministic, the real challenge of the algorithm lies in the method of calculating the constraints.…”
Section: Optimization Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…2, we begin with the sequential linear programming (SLP) algorithm for RBDO developed in Chan et al (2006Chan et al ( , 2007. Since the objective function is deterministic, the real challenge of the algorithm lies in the method of calculating the constraints.…”
Section: Optimization Algorithmmentioning
confidence: 99%
“…As discussed in Fletcher and Leyffer (2002), similar structure and convergence arguments could be used in creating a filter-based SQP algorithm. In Chan et al (2006), we showed that active set strategies can be integrated with the filter-SQP algorithm to improve the efficiency of the algorithm by only calculating constraints that are likely to be active in the next iteration. For problems with a large number of constraints or computational expensive constraints (such as the probability constraints in RBDO), the active set based algorithm significantly improves the computational efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations